Peningkatan Keamanan Jaringan Virtual Private Network Menggunakan Protokol IKE/IPSEC Berbasis Mikrotik - Annisa Dwi Prameswari; Ronald David Marcus (J-INTECH ( Journal of Information and Technology), 2024)
This research discusses protocols VPN (Virtual Private Network), namely PPTP, SSTP, L2TP, and IPsec, analyzes the authentication methods used in each protocol. The method used in this research is qualitative and involves testing the connectivity, authentication and configuration used in each VPN protocol. The parameters used in this research are configuration complexity, flexibility, security and the time required to connect to the VPN network. In the IKE/IPsec protocol, a comparison authentication analysis between Pre-Shared Key and certificate is carried out. Authentication using certificates is proven to be more secure even though it requires more complicated configuration compared to Pre-Shared Key. . The result of this research is the use of IKE / IPsec protocol has flexibility and good security. The algorithms in this protocol can be selected according to the needs and desired security.